The influence of substance use disorder comorbidity on the treatment response of inpatient adolescents with the diagnosis of first episode psychosis - Eseroglu, Tugba; Yalcin, Ozhan; KILIÇOĞLU, Ali Güven; KILIÇOĞLU, ALİ GÜVEN; Karacetin, Gul (My University, 2019)
Objective: The comorbidity of substance use disorders (SUD) in psychotic disorders are common. In this study, it was aimed to investigate whether there was any difference in treatment choice, duration and treatment benefit in adolescents with first episode psychosis (FEP) diagnosis in the presence of SUD comorbidity. Methods: The study included 56 people aged between 14-18 years who were diagnosed with IAP and hospitalized. The sociodemographic data form was completed by interviewing all the patients and their families. Positive and Negative Syndrome Scale (PANSS), Brief Psychiatric Rating Scale (BPRS), Clinical Global Impression Scale (CGI) and Young Mania Rating Scale were used. After the interview, patients were divided into two groups, one at the lifetime and/or currently being diagnosed with SUD (26 patients) and not (30 patients). Results: In the SUD comorbid group the most frequent used substances were determined as synthetic cannabinoids (46.2%) and cannabis (23.1%). Olanzapine, biperiden and benzodiazepines were more common used in the IAP group, and risperidone was more preferred in the comorbid group. The duration of hospitalization were similar. When the scale scores in the entry and discharge were compared, higher scores were found in the PANNS positive subscale scores in the comorbid group. There was no difference between the two groups when the improvement rates between the entry and discharge scale scores were compared. Conclusion: Studies on the frequency of psychoactive substances use in psychotic disorders are common, but our data on the effect of its on the treatment process are quite limited, especially during adolescent age. In our study, in the presence of SUD comorbidity although there are no differences in the duration of treatment and benefit from the treatment, larger samples and follow-up studies are needed.